Current Ratio, Total Assest Turnover dan Return On Assest sebagai variabel intervening Terhadap Earning Per Share - Otto Bustani; Suheri Suheri (Inovatif: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital dan Kewirausahaan, 2022)
The aimed  for this research is to determine the effect of current ratio, total assets turnover on return on assets. And to determine the effect of current ratio, total assets turn over and return on assets on earning per share on the mining company that listed in Indonesian Stock Exchange year 2014-2016 in Jakarta. Also to determine that current ratio and total assets turn over could be intervenned by reutrn on assets to earning per share. We use a quantitative and assosiative approach on this research. We use  secondary data to collect annually financial statement and also financial ratios for mining company where listed in Bursa Efek indonesia in Jakarta year 2014 – 2016. Sample determination usespurposive sampling. Aanalysis Technic we use is calssic assumption test and multiple linear regression. With statistic Eviews.